Harmonisation of shari’ah and the Convention on the Elimination of All Forms of Discrimination against Women (CEDAW) - Elshobake, Mohammed R M; Harara, Mohammed M K (Centre for Islamisation (CENTRIS), International Islamic University Malaysia (IIUM), 2024)
The Convention on the Elimination of All Forms of Discrimination against Women (CEDAW), adopted by Resolution No. 34/180 of the United Nations General Assembly on December 18, 1979, embraces the principle of eliminating all forms of discrimination against women in political, economic, and social realms. It urges signatory countries towards absolute gender equality, which is inconsistent with Islamic law. This study aims to discuss women's rights under CEDAW and Islamic law as well as the compatibility and conflict between CEDAW and Islamic law. Through the doctrinal research, this article endeavours to shed light on the avenues through which Shari’ah and CEDAW can come up with common ground, fostering a harmonious coexistence that upholds the rights and dignities of women within the context of Islamic law and the broader international legal framework. It is concluded that that Shari’ah offers women comprehensive rights and suggests that harmonisation between Shari’ah and the CEDAW could be achieved through substantial amendments to provisions conflicting with Islamic law or by states ratifying the CEDAW with reservations to articles inconsistent with Islamic law.